ANALISIS PENDAPATAN USAHA DAGANG BUAH SEMANGKA NON BIJI (CITRULLUS LANATUS) DI PASAR INPRES MANONDA KECAMATAN PALU BARAT KOTA PALU - Cici Rahmadhany Papia; Muh Fardhal Pratama (Fakultas Pertanian, Universitas Tadulako, 2022)
The study aimed to understand why fruit traders prefer to sell non-seeded watermelons than seeded one, and to determine the income generated by non-seeded watermelon trading at the Manonda Inpres Market in Palu City. It was conducted using a case study approach with a census technique, where all the population was taken as the research sample in September to November 2021. The study found that fruit traders prefer to sell non-seeded watermelons because there is a higher demand for them compared to seeded watermelons. Additionally, the income generated by non-seeded watermelon trading is higher for both wholesalers and retailers. Specifically, the wholesalers earn IDR 7,984,964.29/month, while retailers earn IDR 6,702,528.65/month. The study provides useful insights into the preferences of fruit traders and the income generated by non-seeded watermelon trading.